KESANTUNAN DALAM PERCAKAPAN PEMANDU WISATA DI UBUD BALI - I Gusti Ayu Agung Dian Susanthi; Anak Agung Istri Manik Warmadewi (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
The politeness of a language is important in providing services such as services in tourism. In providing services in the tourism sector it is certainly important to provide good service as an example of using polite language so that tourists feel comfortable while enjoying tourism. Tourists in this study focused on tour guides, tour guides are one of the jobs associated with guest activities while enjoying their tours in Bali, guests need the services of tour guides to take them on a tour while on vacation in Bali. Ubud is one of the tourism areas that is visited by guests from various parts of the world. Thus, researchers chose the Ubud area as a research location. The tour guide in Ubud is the object of the study. At the first stage, the method used was observation method. In this case the researcher identified the conversation and explored politeness in the conversation between the tour guide and the tourist. At the second stage, the researcher identified the politeness of the language contained in the conversation. The next stage, the researcher used the method of observation, the researcher observed, examined gudiding conversations and examined politeness in English expressions used by tour guides.